ClC-3 regulates the excitability of nociceptive neurons and is involved in inflammatory processes within the spinal sensory pathway - Sierra-Marquez, Juan; Willuweit, Antje; Schöneck, Michael; Bungert-Plümke, Stefanie; Gehlen, Jana; Balduin, Carina; Müller, Frank; Lampert, Angelika; Fahlke, Christoph; Guzman, Raul E. (Frontiers in Cellular Neuroscience, 2022)
ClC-3 Cl-/H+ exchangers are expressed in multiple endosomal compartments and likely modify intra-endosomal pH and [Cl-] via the stoichiometrically coupled exchange of two Cl- ions and one H+. We studied pain perception in Clcn3-/- mice and found that ClC-3 not only modifies the electrical activity of peripheral nociceptors but is also involved in inflammatory processes in the spinal cord. We demonstrate that ClC-3 regulates the number of Nav and Kv ion channels in the plasma membrane of dorsal root ganglion (DRG) neurons and that these changes impair the age-dependent decline in excitability of sensory neurons. To distinguish the role of ClC-3 in Cl-/H+ exchange from its other functions in pain perception, we used mice homozygous for the E281Q ClC-3 point mutation (Clcn3E281Q/E281Q), which completely eliminates transport activity. Since ClC-3 forms heterodimers with ClC-4, we crossed these animals with Clcn4-/- to obtain mice completely lacking in ClC-3-associated endosomal chloride/proton transport. The electrical properties of Clcn3E281Q/E281Q/Clcn4-/- DRG neurons were similar to those of wild-type cells, indicating that the age-dependent adjustment of neuronal excitability is independent of ClC-3 transport activity. Both Clcn3-/- and Clcn3E281Q/E281Q/Clcn4-/- animals exhibited microglial activation in the spinal cord, demonstrating that competent ClC-3 transport is needed to maintain glial cell homeostasis. Our findings illustrate how reduced Cl-/H+ exchange contributes to inflammatory responses and demonstrate a role for ClC-3 in the homeostatic regulation of neuronal excitability beyond its function in endosomal ion balance.